Egg and larval production of Eastern Baltic cod in captivity over one spawning season - Neele Schmidt; Marc M. Hauber; Samuel Hylander; Anssi Laurila; Felix Mittermayer; Jan Dierking (Journal of Fish Biology, 2026)
Eastern Baltic cod ( Gadus morhua ) has experienced a dramatic decline in biomass, distribution, size and condition over recent decades, related to a combination of fishing pressure and environmental stressors. Reduced parental size and condition are known to impact reproductive success, affecting egg quality, fertilization and hatching success and larval survival. However, how these reproductive traits vary throughout the spawning season at the population level remains poorly understood for this stock. To address this knowledge gap, this study investigated egg and larval characteristics of captive Eastern Baltic cod over an entire spawning season. Fish from three different size classes were kept in three separate tanks and allowed to spawn naturally. Eggs were collected daily from April to August, with peak spawning observed in early to mid‐June. We assessed egg and larval size, deformities, thiamine concentration, daily survival and hatching success over time. Our findings revealed high variability in these reproductive traits both across the spawning season and between size groups, without consistent temporal trends. Notably, smaller fish produced the largest eggs with the highest total thiamine concentrations, which contrasts with previous studies linking larger egg size with larger females. At the same time, these eggs showed the lowest survival and hatching rates. The only consistent pattern across all tanks was a positive relationship between egg and larval size, though unrelated to survival. These results suggest higher than expected complexity of reproductive dynamics in Eastern Baltic cod and raise the question whether the stock has undergone a shift in reproductive strategy, possibly reflecting an increased allocation towards egg quality over quantity during the recent period of stock decline.

Warming Causes a Decline in Baltic Sea Coastal Sediment Microbial Abundance - Laura Seidel; Songjun Li; Shahinez Hanna‐Elias; Iryna Rula; Louise Ahlberg; Anders Forsman; Samuel Hylander; Marcelo Ketzer; Mark Dopson (Environmental Microbiology, 2026)
Long‐term ocean warming impacts the marine environment, and these effects will be exacerbated by future climate change affecting, e.g., biogeochemical processes and microbial communities. However, how the sediment microbial cell abundance and live/dead ratio respond to warming is poorly understood. In this study, sediment core samples were collected from a Baltic Sea bay artificially heated on average 5°C for > 50 years above a nearby (control) bay unaffected by the heating. Contrary to the expected increased productivity in the heated bay, qPCR‐based sediment cell abundances showed decreased cell numbers along the sediment depth gradient in the heated bay compared to the control bay. This could reflect that a portion of the cells' metabolic energy was diverted to a heat related stress response rather than being used for replication. In addition, live/dead cell ratios showed no clear differences in either bay suggesting the majority of the cells were alive. Finally, sediment depth gradient 16S rRNA gene sequencing confirmed previous studies, showing that prolonged warming shallows sediment biogeochemical zones and related microbial communities. In conclusion, future climate change related warming will likely decrease microbial cell abundances that form part of the food web base, potentially impacting the entire ecosystem.

Climate warming disrupts zooplankton phenology and overwintering strategies - Ida K. Svendsen; Anders Forsman; Mark Dopson; Emelie Nilsson; Johanna Sunde; Sofia Håkansson; Marcelo Ketzer; Samuel Hylander; Romana K. Salis (Limnology and Oceanography, 2025)
Zooplankton are crucial for food webs and biogeochemical cycles. However, warming associated with climate change may alter their seasonal timing and reproductive strategies. This study investigated how long‐term warming impacted zooplankton (mainly copepods) phenology and overwintering strategies by comparing a Baltic Sea bay, heated by warm water discharge for more than 50 yr, with an unaffected control bay. Field observations showed that copepod and phytoplankton population growth began earlier in the heated bay than in the control bay, suggesting that copepod abundance was driven by both temperature and food availability in the heated bay and by a stronger temperature dependence in the control bay. Resting eggs are normally produced as a life‐history strategy to survive unfavorable environmental conditions. Our laboratory incubation experiment showed fewer dormant resting eggs hatched from the heated bay sediment compared with the control bay, supporting an evolutionary change in overwintering strategy. In conclusion, the results seemed to suggest that copepods adjusted their life‐history in elevated temperatures by relying less on the strategy of using sediment‐stored dormant eggs and instead started their spring development earlier, when phytoplankton food was available. Hence, this study suggests that climate change can shift copepod overwintering strategies, leading to potential cascading effects in the food web and affecting overall biodiversity and productivity.

Turbidity reduces territory defence and exploration in an East African cichlid, Neolamprologus pulcher - Markus Zöttl; Jessica Cuccuru; Adrian Berge; Kristofer Bergström; Henrik Flink; Marc M. Hauber; Samuel Hylander; Francesca Leggieri; Oscar Nordahl; P. Andreas Svensson; Petter Tibblin; Carl Tamario (Animal Behaviour, 2025)

The Role of Temperature in the Termination of Dormancy in Zooplankton - Emma Svahn; Marcus Hall; Samuel Hylander (Marine Ecology, 2025)
Organisms in systems with seasonality require adaptations that enable them to endure harsh conditions and to emerge again at an optimal time to start a new period of production. One such adaptation is dormant eggs in zooplankton. While there is much information on the cues leading to the production of dormant eggs, less is known about the termination and hatching of these eggs, especially among marine zooplankton. Our results from a combined laboratory and field study at a coastal Baltic Sea site showed that hatching in some overwintering copepods was temperature‐dependent, with a threshold‐like initiation between 6°C and 9°C. In contrast, overwintering rotifers hatched in comparable abundances in all temperatures, once a similar amount of degree‐days had been accumulated. The field study demonstrated that nauplii started to appear when temperatures increased above 6.8°C and were more abundant close to the sediment than in surface water in early spring, matching the hatching threshold found in the laboratory. Various rotifers increased in abundance at different times during the spring phenology, but without any differences in abundance between deep and surface waters. Hence, the hatching of zooplankton dormant eggs in this system is temperature‐dependent, likely taxa‐specific, and continued climate change is predicted to have implications for the plankton phenology, mismatches, and food web composition.

Application of Floating Beds Constructed with Woodchips for Nitrate Removal and Plant Growth in Wetlands - Maidul I. Choudhury; Mikk Espenberg; Marc M. Hauber; Kuno Kasak; Samuel Hylander (Water, Air, & Soil Pollution, 2024)
Constructed wetlands and constructed floating wetlands are widely used for nitrogen (N) removal from surface water to combat eutrophication in freshwaters. Two main N removal pathways in freshwaters are plant biomass N uptake and denitrification, i.e. transformation of nitrate (NO 3 -) to nitrous oxide (N 2 O) or nitrogen gas (N 2 ) by different microbes possessing nirK , nirS , nosZI, and n osZII genes. In this study, we tested woodchips-based floating beds (WFBs) as a nature-based and environment-friendly method to remove nitrate-nitrogen (NO 3 -N) from water. Moreover, we tested whether WFBs could support the growth of three selected plant species and the abundance of microbes on plant roots and woodchips as a proxy for WFBs’ denitrification potential. We conducted a greenhouse experiment for 90 days and measured NO 3 -N removal rates from water in WFBs mesocosms during five sampling occasions. Plant biomass production, biomass N uptake, and plant morphology related to N uptake and abundance of denitrifying organisms were measured at the end of the experiment. NO 3 -N removal rates were 29.17 ± 11.07, 28.18 ± 12.62, 25.28 ± 9.90, and 22.16 ± 7.79 mg L –1 d –1 m –2 (mean ± standard deviation) in Glyceria maxima , Juncus effusus , Filipendula ulmaria, and unplanted WFBs treatments, respectively for whole experimental period. N content in above- and belowground biomass of studied species ranged between 0.98 – 1.15 and 1.09 – 1.28 (% dry weight), respectively. Plant relative biomass production was 215 ± 61, 67 ± 18, and 7 ± 17 (% dry weight) for G. maxima , J. effusus and F. ulmaria , respectively. Denitrifiers were detected both on plant roots and woodchips, indicating WFBs’ denitrification potential. Our study highlights that WFBs could be applied to enhance NO 3 -N removal from surface water through plant biomass uptake and denitrification processes. Future studies should consider the long-term in situ application of WFBs for NO 3 -N removal from water.

Enhancing nitrogen removal through macrophyte harvest and installation of woodchips-based floating beds in surface-flow constructed wetlands - Maidul I. Choudhury; Josefin E. Nilsson; Samuel Hylander; Marc Hauber; Per Magnus Ehde; Stefan E.B. Weisner; Antonia Liess (Chemosphere, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Thiamin dynamics during the adult life cycle of Atlantic salmon ( Salmo salar ) - Vittoria Todisco; Emil Fridolfsson; Charlotte Axén; Elin Dahlgren; Maciej J. Ejsmond; Marc M. Hauber; Kjetil Hindar; Petter Tibblin; Markus Zöttl; Linda Söderberg; Samuel Hylander (Journal of Fish Biology, 2024)
Thiamin is an essential water‐soluble B vitamin known for its wide range of metabolic functions and antioxidant properties. Over the past decades, reproductive failures induced by thiamin deficiency have been observed in several salmonid species worldwide, but it is unclear why this micronutrient deficiency arises. Few studies have compared thiamin concentrations in systems of salmonid populations with or without documented thiamin deficiency. Moreover, it is not well known whether and how thiamin concentration changes during the marine feeding phase and the spawning migration. Therefore, samples of Atlantic salmon ( Salmo salar ) were collected when actively feeding in the open Baltic Sea, after the sea migration to natal rivers, after river migration, and during the spawning period. To compare populations of Baltic salmon with systems without documented thiamin deficiency, a population of landlocked salmon located in Lake Vänern (Sweden) was sampled as well as salmon from Norwegian rivers draining into the North Atlantic Ocean. Results showed the highest mean thiamin concentrations in Lake Vänern salmon, followed by North Atlantic, and the lowest in Baltic populations. Therefore, salmon in the Baltic Sea seem to be consistently more constrained by thiamin than those in other systems. Condition factor and body length had little to no effect on thiamin concentrations in all systems, suggesting that there is no relation between the body condition of salmon and thiamin deficiency. In our large spatiotemporal comparison of salmon populations, thiamin concentrations declined toward spawning in all studied systems, suggesting that the reduction in thiamin concentration arises as a natural consequence of starvation rather than to be related to thiamin deficiency in the system. These results suggest that factors affecting accumulation during the marine feeding phase are key for understanding the thiamin deficiency in salmonids.

Seasonal variation and species-specific concentrations of the essential vitamin B1 (thiamin) in zooplankton and seston - Emil Fridolfsson; Carina Bunse; Catherine Legrand; Elin Lindehoff; Sanna Majaneva; Samuel Hylander (Marine Biology, 2019)

Thiamin (vitamin B 1 ) content in phytoplankton and zooplankton in the presence of filamentous cyanobacteria - Emil Fridolfsson; Elin Lindehoff; Catherine Legrand; Samuel Hylander (Limnology and Oceanography, 2018)
Top predators in several aquatic food webs regularly display elevated reproductive failure, caused by thiamin (vitamin B 1 ) deficiency. The reasons for these low‐thiamin levels are not understood and information about the transfer of thiamin from the producers (bacteria and phytoplankton) to higher trophic levels is limited. One main concern is whether cyanobacterial blooms could negatively affect thiamin transfer in aquatic systems. Laboratory experiments with Baltic Sea plankton communities and single phytoplankton species were used to study the effect of filamentous cyanobacteria on the transfer of thiamin from phytoplankton to zooplankton. Experiments showed that the thiamin content in copepods was reduced when exposed to elevated levels of cyanobacteria, although filamentous cyanobacteria had higher levels of thiamin than any other analyzed phytoplankton species. Filamentous cyanobacteria also had a negative effect on copepod egg production despite high concentrations of non‐cyanobacterial food. Phytoplankton species composition affected overall thiamin concentration with relatively more thiamin available for transfer when the relative abundance of Dinophyceae was higher. Finally, phytoplankton thiamin levels were lower when copepods were abundant, indicating that grazers affect thiamin levels in phytoplankton community, likely by selective feeding. Overall, high levels of thiamin in phytoplankton communities are not reflected in the copepod community. We conclude that presence of filamentous cyanobacteria during summer potentially reduces the transfer of thiamin to higher trophic levels by negatively affecting phytoplankton and copepod thiamin content as well as copepod reproduction, thereby lowering the absolute capacity of the food web to transfer thiamin through copepods to higher trophic levels.

Individual changes in zooplankton pigmentation in relation to ultraviolet radiation and predator cues - Martin Brüsin; P. Andreas Svensson; Samuel Hylander (Limnology and Oceanography, 2016)
Copepods are common crustaceans in aquatic systems and one of the most important producers of carotenoid astaxanthin pigments, which can enhance the animals' resistance against potentially damaging ultraviolet radiation (UVR), but at the same time, increases the risk of fish predation. Previous studies have demonstrated that copepods have different pigmentation levels matching the current threat level in terms of UVR and fish occurrence. However, these other studies have quantified population‐levels changes in pigmentation, making it difficult to disentangle the role of individual phenotypic colour changes from that of selection. We quantified carotenoid‐based pigmentation with colorimetric methods, which enabled us to track changes within individual copepods. Two species of copepods, Diaptomus castor and Eudiaptomus gracilis , were exposed to high and low UVR and fish cues in a factorial design. L*a*b* colour values (CIE; Commission International de l'Eclairage) were extracted from digital photographs of each copepod and used as proxies for carotenoid concentration. Our results showed that individual copepods significantly changed their pigmentation in response to both UVR and fish cues within a period of 2 weeks. However, the responses differed between sexes and between adults and juveniles. UVR effects were present in all life‐stages whereas fish effects were only detected in juveniles, with largest responses in D. castor . This confirms that carotenoid pigmentation is a phenotypically plastic trait, and highlights that strategies for trading off risks of UVR and predation differ between males and females as well as between life‐stages.

Adult and offspring size in the ocean: a database of size metrics and conversion factors - Anna B. Neuheimer; Martin Hartvig; Jan Heuschele; Samuel Hylander; Thomas Kiørboe; Karin H. Olsson; Julie Sainmont; Ken H. Andersen (Ecology, 2016)
The purpose of this dataset was to compile adult and offspring size estimates for marine organisms. Adult and offspring size estimates of 408 species were compiled from the literature covering >17 orders of magnitude in body mass and including Cephalopoda (ink fish), Cnidaria (“jelly” fish), Crustaceans, Ctenophora (comb jellies), Elasmobranchii (cartilaginous fish), Mammalia (mammals), Sagittoidea (arrow worms) and Teleost (i.e., Actinopterygii, bony fish). Individual size estimates were converted to standardized size estimates (carbon weight, g) to allow for among‐group comparisons. This required a number of size estimates to be converted and a compilation of conversion factors obtained from the literature are also presented.

Instantaneous threat escape and differentiated refuge demand among zooplankton taxa - Lars‐Anders Hansson; Giuseppe Bianco; Mikael Ekvall; Jan Heuschele; Samuel Hylander; Xi Yang (Ecology, 2016)
Most animals, including aquatic crustacean zooplankton, perform strong avoidance movements when exposed to a threat, such as ultraviolet radiation (UVR). We here show that the genera Daphnia and Bosmina instantly adjust their vertical position in the water in accordance with the present UVR threat, i.e., seek refuge in deeper waters, whereas other taxa show less response to the threat. Moreover, Daphnia repeatedly respond to UVR pulses, suggesting that they spend more energy on movement than more stationary taxa, for example, during days with fluctuating cloud cover, illustrating nonlethal effects in avoiding UVR threat. Accordingly, we also show that the taxa with the most contrasting behavioral responses differ considerably in photoprotection, suggesting different morphological and behavioral strategies in handling the UVR threat. In a broader context, our studies on individual and taxa specific responses to UVR provide insights into observed spatial and temporal distribution in natural ecosystems.

Concentrations of sunscreens and antioxidant pigments in A rctic C alanus spp. in relation to ice cover, ultraviolet radiation, and the phytoplankton spring bloom - Samuel Hylander; Thomas Kiørboe; Pauline Snoeijs; Ruben Sommaruga; Torkel Gissel Nielsen (Limnology and Oceanography, 2015)
Arctic zooplankton ascend to shallow depths during spring to graze on the yearly occurring phytoplankton bloom. However, in surface waters they are exposed to detrimental ultraviolet radiation (UVR) levels. Here, we quantified concentrations of substances known to have UVR‐protective functions, namely mycosporine‐like amino acids (MAAs) and the carotenoid astaxanthin, from March to May in Calanus finmarchicus , Calanus glacialis and Calanus hyperboreus . Ice cover was 100% in the beginning of March, started to break up during April and was gone by the end of May. UVR‐exposure in the water column was tightly linked to the ice conditions and water UVR‐transparency was up to 6 m (depth where 1% radiation remains). Concentrations of MAAs in C. finmarchicus and C. glacialis increased sharply during ice break‐up and peaked concurrently with maximum chlorophyll a (Chl a ) levels. MAA‐concentrations in C . hyperboreus increased later in accordance with its later arrival to the surface. The concentration of astaxanthin increased in all three species over time but there was no synchrony with ice conditions or the phytoplankton bloom. Even though only the upper 6 m of the water column was affected by UV‐radiation, MAAs in the copepods were tightly correlated to the UV‐threat. Hence, changes in ice cover are projected to have a large impact on the UVR‐exposure of zooplankton emphasizing the importance of the timing of zooplankton ascent from deep waters in relation to the phytoplankton bloom and the ice break‐up.

Diel vertical migration, size distribution and photoprotection in zooplankton as response to UV‐A radiation - Mikael T. Ekvall; Samuel Hylander; Tim Walles; Xi Yang; Lars‐Anders Hansson (Limnology and Oceanography, 2015)
The transparency regulator hypothesis (TRH) proposes that ultraviolet radiation (UVR) is a main driving force behind diel vertical migration (DVM) of zooplankton in clearwater systems. While previous studies have mainly studied DVM in relation to the TRH on a spatial scale across systems we here focus on long‐term trends in a single system in order to assess if UVR explains observed patterns in DVM. We show that the strength of DVM in Daphnia is to a large extent explained by UVR and we demonstrate a tipping point at which the UVR intensity drastically affects the strength of DVM in Daphnia . In contrast, the strength of DVM could not be explained by the level of UVR among calanoid copepods. The amount of photoprotective compounds did not differ between zooplankton found at different depths indicating that zooplankton do not change their vertical position in relation to the amount of accumulated photoprotective compounds. In addition, we show that both Daphnia and calanoid copepods display patterns of size structured migration.

Vertical distribution and pigmentation of Antarctic zooplankton determined by a blend of UV radiation, predation and food availability - Samuel Hylander; Lars-Anders Hansson (Aquatic Ecology, 2013)

Glacial clay affects foraging performance in a Patagonian fish and cladoceran - Mikael Jönsson; Lynn Ranåker; Alice Nicolle; Peter Ljungberg; Tony Fagerberg; Samuel Hylander; Therese Jephson; Karen Lebret; Jessica von Einem; Lars-Anders Hansson; P. Anders Nilsson; Esteban Balseiro; et al. (Hydrobiologia, 2011)

Complementary UV protective compounds in zooplankton - Samuel Hylander; Wiebke J. Boeing; Wilhelm Granéli; Jan Karlsson; Jessica von Einem; Kelly Gutseit; Lars-Anders Hanssona (Limnology and Oceanography, 2009)
Zooplankton accumulate several groups of photoprotective compounds to shield against damaging ultraviolet radiation (UV). One of these groups, the carotenoids, makes the animals more conspicuous to visually hunting predators, whereas others, such as the mycosporine‐like amino acids (MAAs) may not. The blend of photoprotective compounds is therefore important for the UV defense but also for the ability to escape predation through crypsis. Here we assess laboratory and field data from different latitudes to examine how UV, predation threat, and pigment availability (in food) affects the mixture of UV‐protective compounds in copepods. Overall, the blend of MAAs and carotenoids was partly explained by the availability of MAAs in the food, the UV‐threat, and the presence of predators. Copepods upregulated their MAA content when UV threat was increasing (i.e., if MAAs were abundant in food), and in field data this accumulation only occurred at high levels of predation threat. If MAAs were scarce, copepods instead compensated with higher carotenoid accumulation. However, when there was a high predation threat this carotenoid compensatory effect was disadvantageous, and low concentrations of both MAAs and carotenoids at high UV‐threat resulted in lower reproduction. In all, these results showed that carotenoids and MAAs are complementary substances, i.e., one is high when the other is low, and copepods are, hence, able to adjust their blend of different UV‐protective compounds to optimize their defenses to the threats of UV and predation. These defense systems may buffer against direct food‐web interactions and help the zooplankton to survive in environments with high UV threat.

Zooplankton vertical migration and plasticity of pigmentation arising from simultaneous UV and predation threats - Samuel Hylander; Niklas Larsson; Lars-Anders Hansson (Limnology and Oceanography, 2009)
We assessed how zooplankton (copepods) handle the simultaneous threats of predators and ultraviolet (UV) radiation and whether they respond with changes in pigmentation, vertical migration, or both. We found weak vertical migration among copepods in response to UV stress, and this response was not apparently influenced by predation risk. Exposure to high levels of UV radiation caused copepods to retain pigments in the absence of a predation threat. When exposed to predation threat, they reduced their pigmentation regardless of UV level. Thus, they ranked predation as a threat more severe than UV radiation. Reducing the protective pigment level in response to predation in a situation in which UV radiation is high may, however, lead to higher mortality.